Realization of Law Number 6 of 2014 through the Role of Management of Village-Owned Enterprises - Sami, Delfian (Cattleya Darmaya Fortuna, 2024)
This study aims to analyze the role of the village government in realizing Law Number 6 of 2014 concerning Villages through the management of Village-Owned Enterprises (BUMDes) in Soguo Village, Bolaang Uki District, South Bolaang Mongondow Regency. The research method used is qualitative descriptive with data collection techniques through observation and interviews, as well as primary and secondary data sources. The results of the study show that the village government has three important roles in community empowerment through BUMDes, namely as a regulator, dynamizer, and facilitator. As a regulator, the village government is tasked with establishing policies that support the management of BUMDes so that they can operate in accordance with the provisions of Law No. 6 of 2014. As a dynamizer, the village government encourages active community participation in the BUMDes management process and strives to overcome various obstacles in development. As a facilitator, the village government provides support in the form of training, guidance, and resources needed to increase community capacity and the sustainability of BUMDes. However, there are inhibiting factors in the empowerment of BUMDes in Soguo Village, such as limited funds and low levels of community participation, which need to be considered in formulating policies and strategies for the development of BUMDes in the future. This research is expected to be the basis for the formulation of more effective policies in supporting the development of BUMDes and community empowerment at the village level.